ANALISIS PEMBACAAN SIGHAT TAKLIK TALAK SEBAGAI ALASAN PERCERAIAN MENURUT HUKUM ISLAM - NIM. A1012201109, TOMI ANGGARA PUTRA (Jurnal Fatwa Hukum, 2024)
ABSTRACT  The reading of the sighat taklik talaq as a reason for divorce, where the reading of the sighat taklik talaq itself is done at the time of the marriage contract. In Islamic law it is not regulated whether the reading should be pronounced or read aloud (pronounced) or not read aloud, sighat taklik talaq is only known as a form of agreement. So that is the reason for the writer to know clearly about the reading of sighat taklik talaq as a reason for divorce according to Islamic law. The purpose of this research is to know and analyze about the reading of sighat taklik talaq as a reason for divorce in Islamic law. To find out and analyze the legal consequences of reading sighat taklik talaq as a reason for divorce according to Islamic law.The method used in the research uses the Normative legal research method, by using the legal approach (statute approach) and Conceptual Approach (conceptual approach). The type of data used in this research uses secondary data with data collection techniques using Library Research. That is, the collection of this data is done by examining existing documents, namely by collecting legal materials in the form of Islamic Law Compilation rules, journals, and other sources related to the author's research theme.The result of this research is that Taklik talaq is not something that must be recited when the marriage takes place, but an option. However, once pronounced taklik talaq cannot be withdrawn or changed, even with the consent of the wife and husband. Then the legal consequences that arise when the husband violates the contents of the sighat taklik divorce agreement that he uttered verbally or with voice or without uttering is the fall of ba'in sughra divorce, which is to break the marital relationship of husband and wife.Keywords: Divorce, Talaq, Islamic Law    ABSTRAKPembacaan sighat taklik talak sebagai alasan perceraian, yang mana pembacaan sighat taklik talak itu sendiri dilakukan pada saat akad perkawinan. Didalam hukum Islam tidak diatur apakah pembacaannya harus dilafalkan atau dibacakan dengan bersuara (diucapkan) atau tidak dibacakan dengan bersuara, sighat taklik talak hanya dikenal sebagai bentuk perjanjian. Maka hal tersebut menjadi alasan penulis untuk mengetahui secara jelas mengenai pembacaan sighat taklik talak sebagai alasan perceraian menurut hukum Islam.Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis mengenai pembacaan sighat taklik talak sebagai alasan perceraian dalam hukum Islam. Untuk mengetahui dan menganalisis akibat hukum pembacaan sighat taklik talak sebagai alasan perceraian menurut hukum Islam.Metode yang digunakan dalam penelitian menggunakan metode penelitian hukum Normatif, dengan menggunakan pendekatan undang-undang (statute approarch) dan Pendekatan Konsep (conceptual appoarch). Jenis data yang digunakan dalam penelitian ini menggunakan data sekunder dengan teknik penggumpulan data menggunakan Library Research. Yakni Pengumpulan data ini dilakukan dengan cara meneliti dokumen-dokumen yang ada yaitu dengan mengumpulkan bahan-bahan hukum berupa, aturan Kompilasi Hukum Islam, jurnal-jurnal, sumber lain yang berkaitan dengan tema penelitian penulis.Hasil dari penelitian ini adalah Taklik talak bukan suatu hal yang wajib dibacakan saat pernikahan dilangsungkan, akan tetapi sebuah pilihan. Namun sekali diucapkan taklik talak tidak dapat ditarik kembali atau diubah, meskipun dengan persetujuan pihak istri dan suami. Kemudian akibat hukum yang timbul apabila suami melanggar isi perjanjian sighat taklik talak yang diucapkannya secara lisan atau dengan bersuara atau dengan tidak diucapkan adalah jatuhnya talak ba"™in sughra, yakni memutuskan hubungan perkawinan suami istri.Kata Kunci : Perceraian, Taklik talak, Hukum Islam